2009
DOI: 10.1111/j.1365-2133.2009.09139.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical severity and prognosis of hand eczema

Abstract: Overall, the disease had improved 6 months after the dermatological examination: nevertheless, many patients continued to have significant symptoms. Dermatologists should pay special attention to patients with frequent eruptions and to unskilled workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
8
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 34 publications
5
79
8
5
Order By: Relevance
“…The median age of the cohort was 41 years (age range 18-84 years) at baseline, 65.2% (« = 521) were women and 34.8% (« = 278) were men (6). The present clinical severity, assessed by the patients using the self-administered photographic guide, was reported as severe or very severe by 25.3% of the patients, 35.0% had moderate symptoms, 33.1% had mild symptoms and 6.7% reported being free of hand eczema (6). In all, 697 patients (response rate il.2%) completed all 10 questions on the DLQI questionnaire at baseline; 571 individuals completed the DLQI at follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median age of the cohort was 41 years (age range 18-84 years) at baseline, 65.2% (« = 521) were women and 34.8% (« = 278) were men (6). The present clinical severity, assessed by the patients using the self-administered photographic guide, was reported as severe or very severe by 25.3% of the patients, 35.0% had moderate symptoms, 33.1% had mild symptoms and 6.7% reported being free of hand eczema (6). In all, 697 patients (response rate il.2%) completed all 10 questions on the DLQI questionnaire at baseline; 571 individuals completed the DLQI at follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in DSG4 (encoding desmoglein 4) have been found to be responsible for LAHl (5). Kazantseva et al (6) reported deletion mutations in LIPH leading to LAH2. Pasternack et al (7) reported disruption of LPAR6 in families affected with LAH3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prompt treatment is recommended because hand eczema has a tendency to become chronic, in which case resistance to topical treatment is common. 19 Current treatment strategies are largely based on clinical experience and may differ from country to country. 7,8,20 Few therapies have been evaluated in randomized, controlled trials, 21 and the trials that have been conducted typically have not distinguished types of eczema.…”
Section: Hand Eczemamentioning
confidence: 99%
“…In patients with occupational hand eczema, only 28-40% reported total recovery [5,6]. Poor prognosis and persistence of hand eczema have been found to be correlated with severe initial disease and its duration before diagnosis [6,7]. In European countries, skin diseases are among the top three in the list of occupational diseases [8].…”
Section: Introductionmentioning
confidence: 99%